2010
DOI: 10.1007/s11999-010-1451-0
|View full text |Cite
|
Sign up to set email alerts
|

Combining C-reactive Protein and Interleukin-6 May Be Useful to Detect Periprosthetic Hip Infection

Abstract: Background The sensitivity and specificity to detect periprosthetic infection of the different methods have been questioned, and no single laboratory test accurately detects infection before revision arthroplasty. Questions/purposes We asked whether preoperative C-reactive protein (CRP) and interleukin-6 (IL-6) could lead to similar sensitivity, specificity, and predictive values as our previous results obtained with intraoperative frozen section (FS) in revision total hip arthroplasty (THA). Methods We prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 28 publications
2
42
1
5
Order By: Relevance
“…The predictive power of the CRP value in our study was less than that reported by other authors [9,46,51]. At a cutoff point of 10 mg/L Schinsky et al [46], Tohtz et al [51], and Buttaro et al [9] regarded the CRP level as an important diagnostic parameter and found a sensitivity between 58% and 94%, specificity between 80% and 91%, PPV between 55% and 61%, NPV between 82% and 96%, and accuracy between 73% and 78%.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…The predictive power of the CRP value in our study was less than that reported by other authors [9,46,51]. At a cutoff point of 10 mg/L Schinsky et al [46], Tohtz et al [51], and Buttaro et al [9] regarded the CRP level as an important diagnostic parameter and found a sensitivity between 58% and 94%, specificity between 80% and 91%, PPV between 55% and 61%, NPV between 82% and 96%, and accuracy between 73% and 78%.…”
Section: Discussioncontrasting
confidence: 87%
“…At a cutoff point of 10 mg/L Schinsky et al [46], Tohtz et al [51], and Buttaro et al [9] regarded the CRP level as an important diagnostic parameter and found a sensitivity between 58% and 94%, specificity between 80% and 91%, PPV between 55% and 61%, NPV between 82% and 96%, and accuracy between 73% and 78%. Moreover, the AAOS Work Group pointed out in their guidelines that aspiration or biopsy should be done only if the CRP is increased [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously studied the combination of serum CRP and interleukin-6 to detect PJI and compared with frozen section. Serum CRP and interleukin-6 provided similar sensitivity, specificity, and positive predictive values as the frozen section [5]. However, limitations of the interleukin-6 diagnostic method include high cost and relative lack of availability: in our institution, for logistic reasons, all IL-6 samples were saved and performed intermittently in batches.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно результатам наших исследований, со стороны цитокинов наблюдалась различ-ная динамика в зависимости от особенностей течения послеоперационного периода. Наи-более активным показал себя IL-6, цитокин, являющийся общепризнанным маркером гнойно-воспалительного процесса, включая перипротезную инфекцию [8,9,10].…”
Section: Discussionunclassified